Efficacy of lofexidine for mitigating opioid withdrawal symptoms: results from two randomized, placebo-controlled trials. (1st January 2020) - Alam, Danesh; Tirado, Carlos; Pirner, Mark; Clinch, Thomas
Abstract: Objectives: Fear of opioid withdrawal syndrome (OWS) often dissuades opioid discontinuation. Lofexidine is an FDA-approved, alpha2 -adrenergic receptor agonist for treatment of OWS. Pivotal trial results from the per-protocol statistical analyses have been published. However, the FDA prescribing information presents these efficacy results using a different, standardized statistical approach that does not transform data or impute missing values. This analysis is easier to interpret and allows comparison across studies. This reanalysis is presented here. Methods: Studies were double-blind, placebo-controlled for 7 days in Study 1 and 5 days in Study 2. Opioid-dependent adults received placebo or lofexidine; efficacy was assessed using the Short Opioid Withdrawal Scale of Gossop (SOWS-G) daily. Results: Study 1 ( N = 602) mean SOWS-G scores were 6.1 (SE: 0.35), 6.5 (SE: 0.34), and 8.8 (SE: 0.47) over Days 1–7 for lofexidine 2.88 mg/day, 2.16 mg/day, and placebo, respectively (for 2.88, p < .0001; for 2.16 mg, p < .0001). Study 2 ( N = 264) mean SOWS-G scores were 7.0 (SE: 0.44) and 8.9 (SE: 0.48) over Days 1–5 for lofexidine 2.16 mg/day and placebo, respectively ( p = .0037). Median time to treatment discontinuation was approximately 2 days later with lofexidine treatment than with placebo and significantly more lofexidine-treated subjects completed the studies. Hypotension and bradycardia were more common with lofexidine. More placebo subjects withdrew prematurely for lack of efficacy. Conclusion: This simplified analysis confirmed previous per-protocol results, that lofexidine better reduces OWS severity and increases retention compared with placebo in opioid-dependent adults. These results are robust and comparable across studies using various methods of analysis. ClinicalTrials.gov identifier: Study 1, NCT01863186; Study 2 NCT00235729. URL: https://clinicaltrials.gov/